More on Three-Dimensional Systems of Rational Difference Equations - Liu Keying; Zhao Zhongjian; Li Xiaorui; Li Peng (Discrete Dynamics in Nature and Society)
We are concerned with a kind of three-dimensional system of rational difference equations, given by Kurbanli (2011). A new expression of solution of the system is presented, and the asymptotical behavior is described. At the same time, we also consider a different system and obtain some results, which expand the study of such a kind of difference equations and the method can be applied to other systems.